A spatial inventory of freshwater macroinvertebrate occurrences in the Guineo-Congolian biodiversity hotspot - Emmanuel O. Akindele; Abiodun M. Adedapo; Oluwaseun T. Akinpelu; Esther D. Kowobari; Oluwatosin C. Folorunso; Ibrahim R. Fagbohun; Tolulope A. Oladeji; Olanrewaju O. Aliu; Oluwatobiloba S. Adenola; Babasola W. Adu; Francis O. Arimoro; Sylvester S. Ogbogu; et al. (Scientific Data)
Abstract The Guineo-Congolian region, extending from Guinea in West Africa to the central part of Africa, is considered an important biodiversity hotspot in the Afrotropics. Aside from the underreporting and underestimation of freshwater ecosystems, the challenges regarding incorrect coordinates and taxonomical inaccuracies in freshwater species occurrence data pose another major hurdle that may hinder freshwater conservation efforts in the hotspot. Hence, for any biogeographic analysis, species distribution modelling or conservation initiative, it is crucial to use datasets that are, to the largest possible extent, free of spatial and taxonomic errors. We present the final output of 8,809 occurrences consisting of 4 phyla, eight classes, 32 orders, and 1,104 species. We also added the Hydrography90m stream network attributes to the macroinvertebrate occurrence records, such that the data spans across 2,890 sub-catchments and Strahler stream orders 1–12. These records are considered valid and can be used for biogeographic analysis of freshwater macroinvertebrates in this important yet understudied freshwater biodiversity hotspot.